Sustainable anti-consumption of clothing: A systematic literature review - Essi Vesterinen; Henna Syrjälä (Cleaner and Responsible Consumption, 2022)
The fashion system constitutes one of the most unsustainable industries. In response, the majority of the sustainability research has concentrated on finding ways to boost acquisition of greener products, whereas more recent research has regarded anti-consumption as the pathway to sustainable consumption. However, there appears to be a conceptual ambiguity in the relationship between the constructs of sustainable consumption and anti-consumption. In addition, it is unclear which phases of consumption – acquisition, usage and/or disposal – are to be opposed when one opposes consumption. To clarify these ambiguities, a systematic literature review of the concepts relating to sustainable anti-consumption of clothing is conducted. In the review, 58 papers are identified and analysed to construct a relational framework of the concepts manifesting anti-consumption of clothing from an environmental sustainability perspective, and with respect to the cycle of consumption. The analysis shows that the multitude of overlapping concepts aim at decreasing either acquisition or disposal, but are not against usage. On the contrary, the analysis emphasises how by intensifying and prolonging the usage, it is possible to decrease acquiring and disposing of clothing, and slow down the cycle of fashion. In this way, the current research constructs conceptual and societal contributions that highlight clearer guidelines for consumers to redirect their behaviour and to companies to develop their business models in a way that releases usage from the negative connotations of consumption.